Impairment of hepatic and renal functions by 2,5-hexanedione is accompanied by oxidative stress in rats (2014)
2,5-Hexanedione (2,5-HD) is the toxic metabolite of n-hexane which is widely used as solvent in numerous industries. The present study elucidated the precise mechanism of 2,5-HD in hepatorenal toxicity by determining the involvement of oxidative stress in rats. Adult maleWistar rats were exposed to 0, 0.25, 0.5, and 1% 2,5-HD in drinking water for 21 days. Exposure to 2,5-HD caused liver and kidney atrophy evidenced by significant elevation in serum aminotransferases, alkaline phosphatase, albumin, bilirubin, urea, creatinine, and electrolytes levels compared with control. The marked dose-dependent increase in total cholesterol (TC), triglyceride (TG), and low-density lipoprotein (LDL) was accompanied with significant decrease in high-density lipoprotein (HDL) levels in 2,5-HD-exposed animals when compared with the control. Administration of 2,5-HD significantly diminished glutathione (GSH) level but increased the activities of superoxide dismutase (SOD), catalase, glutathione peroxidase (GPx), and glutathione-Stransferase (GST) concomitantly with marked elevation in hydrogen peroxide (H2O2) and malondialdehyde (MDA) levels in liver and kidney of the treated groups compared with control. These findings suggest that undue exposure to 2,5-HD at environmentally relevant levels may impair liver and kidney functions through induction of oxidative stress.